IMPLEMENTASI FRAMEWORK ITIL VERSI 3 PADA EVALUASI MATURITAS MANAJEMEN LAYANAN SISTEM INFORMASI MYTELKOMSEL - Yuli Maharetta Arianti; Weda Adistianaya Dewa (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2022)
ABSTRAK Mytelkomsel is a smartphone-based application that is used to meet the needs of Telkomsel customers. Telkomsel is one of the largest cellular telecommunications operators in Indonesia. In the digital era like today, many people use smartphone technology in carrying out their activities. This study aims to determine the performance or quality of information system service management used in the MyTelkomsel application by comparing the level of information technology maturity in the current condition (Current Maturity) and the expected condition (Expected Maturity). The results of this study are gap analysis and recommendations that can be used as an alternative in making improvements to the quality of information technology services. This information technology audit uses the ITIL Version 3 framework. The data was obtained through observation in the form of an online questionnaire with a total of 50 respondents. The conclusion is that the average maturity level score is 3.83 and is included in the Managed and Measurable category with a gap of 0.2. The maturity level value of 3.83 can be defined as a system that can measure and monitor existing procedures so that they are easily handled if deviations occur, and also the processes in the company have been carried out properly and consistently. Kata Kunci : itil, mlsi, maturity level, gap, mytelkomsel.